Um Mecanismo para Compartilhamento de Recursos em Nuvens Colaborativas Baseado na Credibilidade dos Usuários - Sadok, Hugo (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
Collaborative clouds bring the elasticity advantages from traditional clouds to users with few resources, as long as they contribute with their idle resources. Nevertheless, when demand for resources exceeds supply, conflicts arise and each user allocation must be defined. In this work, we propose an allocation mechanism that guarantees resource utilization efficiency while encouraging collaboration. Using game theory, we demonstrate the mechanism properties by defining a model based on a Bayesian setting. In such setting, users constantly decide the amount of resources to either contribute, or request, from the collaborative cloud. Moreover, we use simulations with the Google cloud dataset to verify the mechanism. The results show an increase in the number of served requests up to approximately three times compared to not using the mechanism.